Durability of Marine Concretes with Nanoparticles under Combined Action of Bending Load and Salt Spray Erosion - Zhang Maohua; Lv Zhengyi; Cui Jiyin; Tian Zenong; Li Zhiyi (Advances in Materials Science and Engineering)
The coupling effect of bending load and salt spray erosion during the service of a sea-crossing bridge accelerates the deterioration and durability of concrete and dramatically reduces the load-carrying capacity of the bridge. The effects of nanoparticles on the durability of marine concrete exposed to bending loads and salt spray erosion were studied. In this paper, nano-SiO2 and nano-Fe2O3 were mixed into plain concrete. Free chloride ions (Cl−) were titrated at different concrete depths using a four-point loading device and a self-developed salt spray erosion test chamber. Test results showed that chloride ion levels in the tensile and compressive zones for both nanoconcretes were lower than plain concrete at the same timepoint. The optimal mixtures of the two nanoparticles were 2% and 1%, and the improvement of nano-SiO2 was more significant than nano-Fe2O3. Due to the special properties of nanomaterials, they effectively improved the microstructure of concrete and the composition of cement hydration products. This allowed concrete to become more compact, reduced crack generation, increased the difficulty of Cl− migration inside the concrete, and improved the overall durability of marine concrete upon exposure to bending loads and salt spray erosion.